Safety of teaching endoscopic ultrasound-guided gastroenterostomy (EUS-GE) can be improved with standardization of the technique - Park, Kenneth H.; Rosas, Ulysses S.; Liu, Quin Y.; Jamil, Laith H.; Gupta, Kapil; Gaddam, Srinivas; Nissen, Nicholas; Thompson, Christopher C.; Lo, Simon K. (Endoscopy International Open, 2022)
Background and study aims Endoscopic ultrasound-guided gastroenterostomy (EUS-GE) is a novel technique developed to manage gastric outlet obstruction (GOO). It involves creating a fistula between the stomach and the proximal small bowel using an electric cautery-enhanced lumen-apposing metal stent (ECE-LAMS) with EUS guidance. We aimed to publish our experience in improving teaching of this technique to practicing endoscopists with a wide range of experience by comparing the outcomes before and after standardization of procedural steps.Methods All EUS-GEs performed for inoperable GOO at a single institution from 2014 to 2021 were retrospectively analyzed. The technique was taught by one experienced endoscopist with prior expertise. Five advanced endoscopists with prior EUS and ECE-LAMS placement experience participated. The impact of standardization on outcomes (clinical and technical success, length of stay [LOS], procedure time, and adverse events [AEs]) was compared.Results A total 41 EUS-GEs were performed (5 before and 36 after standardization) by endoscopists with practice experience ranging from 2 to 13 years. The patient population was similar in age and sex. Standardization was associated with significantly higher rates of technical success (100 % vs 60 %, P = 0.01) and lower peri-procedural AEs (2.8 % vs 40 %, P = 0.03). Two AEs in the pre-standardized group were gastric perforation and gastrocolic fistula creation. One AE in the post-standardized group was gastric perforation. Procedure time, clinical success, and LOS showed improvement, although it was not statistically significant.Conclusions Teaching EUS-GE after standardizing the procedure was associated with a significant increase in technical success and a decrease in AEs irrespective of prior total experiences.